ANTI-CORRUPTION SPECIAL DETACHMENT, IS IT NECESSARY? - Raharjo, Agus (Faculty of Law, Universitas Jenderal Soedirman, 2017)
Corruption, being one of the powerful words, contains an astonishing power. Various ways to eradicate it from changing the constitution to the formation of extra judicial institutions failed; it is just strengthening its existence instead. Finally, the discourse of the formation of Anti-Corruption Special Detachment (Densus Tipikor) is rolled out by the Chief of Police. The discourse of this formation indicates that the existence of corruption rather than weakening can even be said to be increasingly rampant......